2022
DOI: 10.3390/nano12234319
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Implications Associated with the Development of Nanotechnology: From Synthesis to Disposal

Abstract: Nanotechnology remains under continuous development. The unique, fascinating, and tunable properties of nanomaterials make them interesting for diverse applications in different fields such as medicine, agriculture, and remediation. However, knowledge about the risks associated with nanomaterials is still poorly known and presents variable results. Furthermore, the interaction of nanomaterials with biological systems and the environment still needs to be clarified. Moreover, some issues such as toxicity, bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 226 publications
(266 reference statements)
0
1
0
Order By: Relevance
“…Recent life-cycle assessment studies showed advantages of nanofertilizers of different micronutrients over conventional fertilizers [ 50 ]. Bottlenecks for a global application of fertilizers based on nanotechnology are improvement of efficiency [ 51 ] and uncertainties about their transformation processes in the soil and the derived environmental impact [ 52 ].…”
Section: Illustrating the Functions Of Soil: An In-depth Perspectivementioning
confidence: 99%
“…Recent life-cycle assessment studies showed advantages of nanofertilizers of different micronutrients over conventional fertilizers [ 50 ]. Bottlenecks for a global application of fertilizers based on nanotechnology are improvement of efficiency [ 51 ] and uncertainties about their transformation processes in the soil and the derived environmental impact [ 52 ].…”
Section: Illustrating the Functions Of Soil: An In-depth Perspectivementioning
confidence: 99%